2020
DOI: 10.3389/fimmu.2020.02054
|View full text |Cite
|
Sign up to set email alerts
|

Mucins in Intestinal Mucosal Defense and Inflammation: Learning From Clinical and Experimental Studies

Abstract: Throughout the gastrointestinal (GI) tract, a distinct mucus layer composed of highly glycosylated proteins called mucins plays an essential role in providing lubrication for the passage of food, participating in cell signaling pathways and protecting the host epithelium from commensal microorganisms and invading pathogens, as well as toxins and other environmental irritants. These mucins can be broadly classified into either secreted gel-forming mucins, those that provide the structural backbone for the mucus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
194
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(204 citation statements)
references
References 211 publications
(298 reference statements)
7
194
0
3
Order By: Relevance
“…Given the fact that endotoxemia is one of the common features of IBD and metabolic disorders, we hypothesized that an impaired intestinal barrier function caused by DSS treatment triggers LPS-induced systemic inflammation that could lead to disturbed energy homeostasis. Several studies have shown that in the pathogenesis of DSS-induced colitis, the intestinal epithelial barrier dysfunction is associated with the disruption of tight junction proteins 45 , 46 , as well as mucus layer proteins 47 . Mice with DSS-induced colitis used in this study consistently showed decreased expression of ZO-1, occludin, MUC2, and MUC13 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that endotoxemia is one of the common features of IBD and metabolic disorders, we hypothesized that an impaired intestinal barrier function caused by DSS treatment triggers LPS-induced systemic inflammation that could lead to disturbed energy homeostasis. Several studies have shown that in the pathogenesis of DSS-induced colitis, the intestinal epithelial barrier dysfunction is associated with the disruption of tight junction proteins 45 , 46 , as well as mucus layer proteins 47 . Mice with DSS-induced colitis used in this study consistently showed decreased expression of ZO-1, occludin, MUC2, and MUC13 (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, similar changes have been described in patients suffering from NEC [16][17][18]22], which suggests that a loss of goblet cells in utero may predispose to NEC development. Reduced goblet cell numbers are associated with a disturbed mucus layer [39] and, thus, a reduced intestinal barrier function, which makes a neonate upon birth more vulnerable during the crucial period of microbial colonization. In addition, the increase of CHOP-positive cells in the crypt at 8-15 d after IA LPS exposure implies that the intestine is prone to a second wave of apoptosis, either following ongoing (intrauterine) inflammation or after additional postnatal inflammatory hits such as mechanical ventilation [40] or sepsis [41].…”
Section: Discussionmentioning
confidence: 99%
“…So, intestinal epithelial disorder may occur in diarrhea mice in this study. Intestinal epithelial disorder is one of the pathological features of functional bowel disease including stress-related diarrhea ( Grondin et al, 2020 ; Kim et al, 2020 ). The overall trend of microbiota community structure is an increase in pathogenic bacteria and a decrease in beneficial bacteria in both intestinal mucosa and intestinal contents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we predicted the function of bacterial genes and found that there were disorders of amino acid metabolism, including the amino acid nitrogen fixation pathway, caused by microbiota in the intestinal mucosa. The results showed that bacterial genes mainly induced intestinal inflammation through the FoxO signaling pathway ( Douglas et al, 2015 ) and MAPK signaling pathway ( Grondin et al, 2020 ) and participated in neural response. It is suggested that the metabolic activities of intestinal microbiota are involved in the brain–gut nerve response, including tryptophan metabolism.…”
Section: Discussionmentioning
confidence: 99%